2013
DOI: 10.1117/12.2023033
|View full text |Cite
|
Sign up to set email alerts
|

White fluorescent nano-fibers prepared by periodic organic hetero-epitaxy

Abstract: To preserve the morphological properties of para-hexaphenyl (p-6P) based nano- bers and simultaneously tune their emission wavelength, periodic organic-organic hetero-epitaxy was utilized. Multilayer structures of p-6P and -sexithiophene (6T) have been prepared by hot wall epitaxy and analyzed by scanning force microscopy, uorescence microscopy, X-ray di raction and time resolved spectroscopy. We demonstrate that organic heteroepitaxy can be applied to produce multilayered nano- bers with high crystallinity, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…It has been reported that the emission from 6T/6P heterostacks can be tuned from yellow, red via white to blue by varying the stacking distance [10][11][12][13][14], and that in epitaxially aligned nanofibers grown by the periodic deposition of 6T and 6P the lasing properties of the nanofibers could be tuned from deep blue to the red-orange [15]. In principle, the significant overlap between the spectral range of 6P emission and 6T absorption makes it possible to have efficient resonance energy transfer (RET) between these materials [16], and for the layered 6T/6P system it was observed that the optical properties of these het- erostructures differ considerably from those of the pure materials [10][11][12][13][14][15][16][17]. A characteristic green emission has been observed in the layered system, which adds to the blue and red emission from pristine 6P and 6T, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the emission from 6T/6P heterostacks can be tuned from yellow, red via white to blue by varying the stacking distance [10][11][12][13][14], and that in epitaxially aligned nanofibers grown by the periodic deposition of 6T and 6P the lasing properties of the nanofibers could be tuned from deep blue to the red-orange [15]. In principle, the significant overlap between the spectral range of 6P emission and 6T absorption makes it possible to have efficient resonance energy transfer (RET) between these materials [16], and for the layered 6T/6P system it was observed that the optical properties of these het- erostructures differ considerably from those of the pure materials [10][11][12][13][14][15][16][17]. A characteristic green emission has been observed in the layered system, which adds to the blue and red emission from pristine 6P and 6T, respectively.…”
Section: Introductionmentioning
confidence: 99%